Influence of Psychological Capital on Absorptive Capacity and Knowledge Transfer - Vinícius Costa da Silva Zonatto; Priscila Rodrigues da Silva; Júlia Ziliotto Zanotto; Larissa Degenhart; Luiz Henrique Figueira Marquezan (RACE: Revista de Administração, Contabilidade e Economia, 2022)
Purpose – This research aimed to analyze the influence of psychological capital on the ability to absorb and transfer knowledge of Accounting students. A descriptive, quantitative and survey research was carried out with 235 students from the Accounting Sciences course of a public higher education institution. Methodology/approach – Data collection was carried out by means of a questionnaire and the analysis with the aid of structural equation modeling. Three hypotheses were established, of which one was refuted. Findings – The results demonstrate the direct influence of psychological capital on students' ability to absorb knowledge and an indirect influence of psychological capital on knowledge transfer mediated by absorptive capacity. It was found that students of the Accounting course with higher psychological capital are more likely to develop their absorptive capacity and, later, to transfer knowledge. This evidence shows that when students develop their psychological capital, their ability to absorb new knowledge is enhanced. Under these conditions, their ability to transfer new knowledge is high. Originality/value – This evidence indicates that students' absorptive capacity mediates the relationship between psychological capital and knowledge transfer. This mediation is complete, in which the effects of psychological capital are indirect on knowledge transfer. These results allow us to conclude that students with greater psychological capital are more likely to develop their ability to acquire, assimilate, transform and apply new knowledge, being able to transfer knowledge acquired in the course to their work activities.